1997
DOI: 10.1046/j.1471-4159.1997.68031312.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Several Nitric Oxide‐Generating Compounds on Purified Na+,K+‐ATPase Activity from Porcine Cerebral Cortex

Abstract: Nitric oxide (NO)-generating compounds (NO donors) such as sodium nitroprusside, S-nitroso-N-acetylpenicillamine, S-nitroso-L-glutathione, 3-morpholinosydnonimine (SIN-i), (DL)-(E)-ethyl-2-[(E)-hydroxyimino] -5-nitro-3-hexenamide, and i -hydroxy-2-oxo-3-(N-methyl-3-aminopropyl)-3-methyl-i -triazene inhibited the Na~,K~-ATPase activity purified from porcine cerebral cortex. NO-reducing or -scavenging agents, such as superoxide dismutase or N-(dithiocarbamate)-Nmethyl-D-glucamine sodium salt, L-ascorbic acid, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Activation of the sGC leads to increased intracellular cGMP concentrations and is believed to mediate many of the physiological effects of NO, even though cGMP-independent effects have also been described (Gupta et al, 1994;Sato et al, 1997). The present study demonstrated increased wholetissue cGMP concentration in response to SNP, apparently by activating sGC in both tissues.…”
Section: (N=6)supporting
confidence: 54%
See 1 more Smart Citation
“…Activation of the sGC leads to increased intracellular cGMP concentrations and is believed to mediate many of the physiological effects of NO, even though cGMP-independent effects have also been described (Gupta et al, 1994;Sato et al, 1997). The present study demonstrated increased wholetissue cGMP concentration in response to SNP, apparently by activating sGC in both tissues.…”
Section: (N=6)supporting
confidence: 54%
“…Nitric oxide has been shown to modulate ion transport in several mammalian tissues, the effect apparently being tissue dependent. Inhibitory effects on the Na + /K + -ATPase have been found in the kidney (opossum, Liang and Knox, 1999;rat, McKee et al, 1994), the choroid plexus (bovine, Ellis et al, 2000), alveolar cells (rat, Guo et al, 1998), aortic endothelial cells (porcine, Gruwel and Williams, 1998), liver (rat, Muriel and Sandoval, 2000) and brain (porcine, Sato et al, 1997). Stimulatory effects have been found in rat trachea (de Oliveira Elias et al, 1999) and rabbit aorta (Gupta et al, 1994).…”
Section: (N=6)mentioning
confidence: 99%
“…In addition, the SNAP-induced increase in cellular volume was observed under isosmotic conditions. Although the exact mechanism was not determined, NO is known to inhibit Na + /K + -ATPase [45,46]. This inhibition may cause an increase in intracellular sodium, leading to water influx through AQP4 [47].…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen phosphorylase activity is stimulated by NO, which would increase tissue levels of glucose-1-phosphate and deplete cellular glycogen (Borgs et al 1996). S-nitrosylation of the sodium pump, which inhibits its activity, may account for membrane depolarization associated with NO-mediated cell death (Sato et al 1997). But how might neural NO gain access to its targets in the presence of millimolar concentrations of glutathione, which would likely sequester freely diffusing cytosolic NO?…”
Section: Discussionmentioning
confidence: 99%